Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/pr400415a
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Signatures of Four Types of Human Arthritis

Abstract: Similar symptoms of the different types of arthritis have continued to confound the clinical diagnosis and represent a clinical dilemma making treatment choices with a more personalized or generalized approach. Here we report a mass spectrometry-based metabolic phenotyping study to identify the global metabolic defects associated with arthritis as well as metabolic signatures of four major types of arthritis--rheumatoid arthritis (n = 27), osteoarthritis (n = 27), ankylosing spondylitis (n = 27), and gout (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 52 publications
(104 reference statements)
1
66
0
5
Order By: Relevance
“…In a similar approach using plasma samples, patients with knee OA were found to have lower levels of arginine 20 . Finally, a metabolomics study that examined serum samples from healthy controls and patients with osteoarthritis, rheumatoid arthritis (RA), ankylosing spondylitis and gout, found that the patients with arthritis could be differentiated from the controls and that each form of arthritis had a distinct metabolite profile 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach using plasma samples, patients with knee OA were found to have lower levels of arginine 20 . Finally, a metabolomics study that examined serum samples from healthy controls and patients with osteoarthritis, rheumatoid arthritis (RA), ankylosing spondylitis and gout, found that the patients with arthritis could be differentiated from the controls and that each form of arthritis had a distinct metabolite profile 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, glucose deprivation or treatment with glycolytic inhibitors such as 2-deoxy-D-glucose and bromopyruvate impaired cytokine secretion, proliferation and migration in FLSs, and glycolytic inhibition by bromopyruvate administered in vivo in a serum-transfer animal model significantly decreased arthritis severity compared with untreated animals 118 . Thus, the increase in lactate detected in metabolomics studies 95,96 could be secondary to the increase in glycolysis in FLSs.…”
Section: Disease-specific Metabolic Pathwaysmentioning
confidence: 97%
“…In a comparison of serum metabolic signatures in OA, RA, ankylosing spondylitis and gout by MS 95 , homoserine, 4,8-dimethylnonanoyl carnitine, glyceraldehyde, lactic acid, dihydroxyfumaric acid and aspartic acid were identified as candidate markers in the four types of arthritis, compared with healthy controls. In another study, with 1 H-NMR characterization of serum samples from patients with established RA, early arthritis and healthy controls, levels of several metabolites, such as 3-hydroxybutyrate, glucose, lactate, and urea, were correlated with the extent of inflammation 96 .…”
Section: Metabolomic Studies In Rheumatic Diseasementioning
confidence: 99%
“…profiled the metabolomic differences of four types of arthritis using GC-MS and LC-MS with 198 annotated features included in statistical analysis. They found elevated energy metabolism and pyruvate to lactate pathway in these samples22. However, none of these studies was focused on using metabolomics to monitor OA progression and treatment.…”
mentioning
confidence: 98%
“…Several metabolomic profiling studies using human subjects and animal models have been reported on the investigation of metabolic responses to OA using biofluids such as urine, plasma and synovial fluids1819202122. Li et al .…”
mentioning
confidence: 99%